NORMS OF TEACHER’S SPEECH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article examines the norms of teacher’s speech as an essential component of professional pedagogical competence. Teacher’s speech is not only a means of transmitting information, but also a powerful educational instrument that shapes students’ thinking, language culture, motivation, emotional safety and communicative behavior. The article analyzes the concept, content, structural elements, formation factors, practical functions, current problems and development strategies of teacher’s speech norms. The study is based on theoretical analysis of Uzbek scholarly works on speech culture, pedagogical communication and literary language norms. Therefore, teacher’s speech norms should be developed systematically through theoretical preparation, practical training, self-analysis, feedback and continuous professional improvement.